High‐Performance Composite Monolith Synthesized via HKUST‐1 Stabilized HIPEs and Its Adsorptive Properties. Issue 11 (13th September 2018) - Yang, Yongxia; Cao, Liqin; Li, Jing; Dong, Yong; Wang, Jide
Abstract: This paper presents a green and facile method for generating a composite monolith. HKUST‐1 (Pickering emulsifier) and PVA (co‐emulsifier), are used to stabilize supercritical carbon dioxide in water as high internal phase emulsion template to prepare interconnected hydrophilic porous monoliths. The effects of HKUST‐1 contents and CO2 densities on the performance of MOF/ polyacrylamide (PAM) polyHIPEs are investigated. The as‐synthesized MOF/PAM composites are characterized by FT‐IR, SEM, XRD, and TGA. The SEM patterns show that the composites are interconnected, the void sizes are 10–80 µm, and the interconnected pore throats are approximately 0.5–25 µm. The rheological and DMA measurement results indicate that the viscoelasticity and mechanical properties of the composites greatly improve after HKUST‐1 is embedded. Furthermore, the adsorptive properties of MOF/PAM to bovine serum albumin (BSA) are studied, and the adsorption capacity of MOF/PAM enhances with the increase in HKUST‐1 content. The adsorption capacity of the composite with 7 wt% HKUST‐1 reached 350.4 mg g −1 in 1.0 g L −1 BSA solution. Abstract : A blue composite monolith with interconnected pore is generated through CO2 /W HIPE emulsion, and amphiphilic MOF is used as a Pickering emulsifier. The adsorption capacity of the composite reaches 350 mg g −1 in 1.0 g L −1 bovine serum albumin solution. The composite monolith is a valuable candidate for immobilized metal affinity chromatography in the analysis and indication of proteins.